Comparison of Chamcham manufactured from cow milk and buffalo milk (Journal of the Bangladesh Agricultural University, 2013)
This experiment was conducted to study quality of Chamcham manufactured from cow milk and to compare it with Chamcham manufactured from buffalo milk and mixture of cow and buffalo milk. Three types of Chamcham were prepared from cow milk(A), buffalo milk(B) and 50% cow +50% buffalo milk(C).In this experiment the quality of prepared Chamcham were evaluated with the help of chemical test. The moisture, total solids, protein, fat, ash and carbohydrate contents of cow milk and buffalo milk Chamcham were showed significant differences (p